The Development Of Digital-Based Reference Books As An Effort Towards A Green Economy - Uswatun Khasanah; Arsyil Waritsman (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
The purpose – of this research is to create a product in the form of a digital-based reference book in an effort toward a green economy. This digital reference book has been tested for feasibility, practicality, and effectiveness as effective student learning tools. The type of research – activity used is the research and development (RnD) method with the 4-D model (Define, Design, Develop, and Disseminate). The media expert assessment of the feasibility of presentation is 4.4 and a percentage of 88%, which means that digital books are very feasible to be used; the material expert validation for the feasibility of presentation is 4.3, and the percentage of validation results by the material expert team is 87%, which means that digital-based reference books are very feasible to be used, and the percentage of overall practicality assessment results obtained is 85% based on the results of the analysis of 30 student responses. Therefore, the conclusion is that digital-based reference books are practical to use as a source of student learning materials. The implication of this research – is that the selection of appropriate learning media significantly affects the student learning process and supports government programs in education towards a green economy.